(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Macro Economics is a branch of economicsdealing with the performance, structure, behavior, anddecision-making of the entire economy. This includes a national, regional, or globaleconomy with micro economics, macroeconomics is one of the two mostgeneral fields in economics.